The Jewish Cemetery of Lucena (Cordoba) - Botella Ortega, Daniel; Casanovas Miró, Jordi (Miscelánea de Estudios Árabes y Hebraicos. Sección Hebreo, 2008)
The discovery, arising from the construction of the Ronda Sur ring road in the town of Lucena (Córdoba province), of a section of a Jewish necropolis in 2007 led to the excavation of some 346 tombs. The new information obtained from the tombs means that the find constitutes a breakthrough in the study of Jewish necropolises from the Andalusi caliphal and post-caliphal period (10th-11th centuries). Furthermore, the discovery of a new Hebrew inscription that had been reused in one of the graves has made the collection of Hebrew epigraphs (few and far between in the Iberian Peninsula and in Andalusia in particular) a little more complete. Lastly, the presence of numerous specimens of tombs comprising a pit and a side chamber, previously only seen in finds dating from the late medieval period, has refined our knowledge of the timespan corresponding to their use.